PSYCHOLOGICAL SUPPORT OF REPRODUCTIVE BEHAVIOR IN INTERPERSONAL RELATIONSHIPS - Biktina, Nasima; Vishnyakov, Alexander; Karymova, Oksana; Logutova, Elena (Revista Inclusiones, 2020)
Objective: to study the features of reproductive attitudes of men and women in relation to reproductive behavior. Methods: questionnaires of systematic and multivariate studies of personality; diagnostics of interpersonal relationships; semantic differential; reproductive attitudes; interviews; semantic psycho-geometric test “Colored shapes”. Results and conclusions. The main motives of reproductive behavior: desire to have a child, love for children, a sense of motherhood, willingness to become a mother. Fathers – procreation. Career and professional activities are compatible with the birth and upbringing of a child. A man has the purpose of material family support.